Changes in spring-mass model characteristics during repeated running sprints - Girard, O.; Micallef, J. P.; Millet, G. P. (European Journal of Applied Physiology, 2011)
This study investigated fatigue-induced changes in spring-mass model characteristics during repeated running sprints. Sixteen active subjects performed 12 × 40 m sprints interspersed with 30 s of passive recovery. Vertical and anterior-posterior ground reaction forces were measured at 5-10 m and 30-35 m and used to determine spring-mass model characteristics. Contact (P < 0.001), flight (P < 0.05) and swing times (P < 0.001) together with braking, push-off and total stride durations (P < 0.001) lengthened across repetitions. Stride frequency (P < 0.001) and push-off forces (P < 0.05) decreased with fatigue, whereas stride length (P = 0.06), braking (P = 0.08) and peak vertical forces (P = 0.17) changes approached significance. Center of mass vertical displacement (P < 0.001) but not leg compression (P > 0.05) increased with time. As a result, vertical stiffness decreased (P < 0.001) from the first to the last repetition, whereas leg stiffness changes across sprint trials were not significant (P > 0.05). Changes in vertical stiffness were correlated (r > 0.7; P < 0.001) with changes in stride frequency. When compared to 5-10 m, most of ground reaction force-related parameters were higher (P < 0.05) at 30-35 m, whereas contact time, stride frequency, vertical and leg stiffness were lower (P < 0.05). Vertical stiffness deteriorates when 40 m run-based sprints are repeated, which alters impact parameters. Maintaining faster stride frequencies through retaining higher vertical stiffness is a prerequisite to improve performance during repeated sprinting.